Investigation of Modern n-Alkanes in Daihai Lake Basin, Northern China: Implications for the Interpretation of Paleoclimate Research - Shen, Zhongwei; Zhang, Zhiping; Chen, Jie; Chen, Lin; Pang, Xin; Chen, Ruijin; Liu, Jianbao; Chen, Shengqian (Frontiers in Earth Science, 2022)
n-Alkanes are one of the most used proxies in lake sediments to reconstruct past climate change. However, the distribution and concentration of n-alkanes are controlled by multiple factors, and their interpretation across northern China has revealed obvious discrepancies. It is therefore important to investigate the controlling factors of n-alkane proxies before using them for paleoclimate reconstruction. In this study, we collected fresh plant leaves, basin surface soils, lake surface sediments and a short sediment core (DH20B) in Daihai Lake basin to analyze the paleoclimate implications of n-alkanes. Our results show that long-chain (C27–C35) n-alkanes in Daihai Lake are dominated by allochthonous sources. The average chain length of long-chain n-alkanes (ACL27–35) and total long-chain n-alkane concentration (∑alklong-chain) of DH20B are significantly correlated with regional summer temperature (r = 0.54, p < 0.01) and summer precipitation (r = 0.41, p < 0.05) over the past 60 years. These results indicate that ACL27–35 and ∑alklong-chain from Daihai Lake sediments have potential to reconstruct past summer temperature and summer precipitation, respectively, because higher summer temperature promotes the synthesis of longer chain n-alkanes to reduce water loss (leading to higher ACL27–35), and increased summer precipitation promotes plant growth (leading to higher ∑alklong-chain). Moreover, we found that human activity significantly affected ∑alklong-chain through cultivation and grazing after 2005. Our findings may have broad significance for paleoclimate reconstruction of other hydrologically closed lakes, highlighting the importance of proxy validation studies.